THE ROLE AND IMPORTANCE OF LITERARY STUDIES IN TEACHING FOREIGN LANGUAGES - Elbayeva Madina Botirovna (Modern American Journals, 2025)
This article explores how literary studies can be effectively utilized to promote foreign language learning and examines various reading methods in depth. As technology continues to develop, enriching the human factor in language learning is crucial. This includes fostering learners' critical thinking and creativity, analyzing characters’ life paths, and enhancing linguistic and grammatical competence through literature.
Keywords: Literary text, thinking critically, improving management skills, enhancing creativity, analyzing and deep working on literacy, boosting language skills grammatically and linguistically.